Coriolis frequency tracking - Henry, MP; Duta, MD; Tombs, MS (2018)
Motion is induced in a conduit such that the conduit vibrates in a major mode of vibration having a major amplitude and a minor mode of vibration having a minor amplitude. The major amplitude is larger than the minor amplitude, the major mode of vibration has a first frequency of vibration and the minor mode of vibration has a second frequency of vibration, and the minor mode of vibration interferes with the major mode of vibration to cause a beat signal having a frequency related to the first frequency of vibration and the second frequency of vibration. The frequency of the beat signal is determined, and the second frequency of vibration is determined based on the determined frequency of the beat signal.